Evaluasi Pembelajaran Daring Matematika pada Siswa Kelas IV SDN Poris Plawad 4 - Huliatunisa, Yayah; Elfrisca, Deva; Barokah, Siti Fadhilatul; Rachma, Salsabila Nabira; Lestari, Nopika Ayu; Nur’alfiah, Siti; Efendi, Herlina (TSAQOFAH, 2022)
This study aims to review how the process of evaluating online learning in fourth grade mathematics subjects at SDN Poris Plawad 4 Tangerang City, using a descriptive qualitative approach, 1 fourth grade mathematics teacher was used as the research subject. Data collection techniques through direct observation, interviews, and documentation studies. The results of the data were analyzed using data condensation steps, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results showed that there were some students who were passive and lacked interest in the online mathematics learning process as well as the emergence of difficulties felt by teachers when evaluating the results of online mathematics learning, such as; not all students have mobile phones to do online learning through the WhatsApp application, quota limitations, and signals. So that it has an impact that students find it difficult to understand the material presented by the teacher, plus the teacher does not master the technology that has developed at this time, which in the end during the online learning process only 1 application is used, namely WhatsApp Group.